Enkele grote lijnen in de Nederlandse stedenbouwgeschiedenis; Een vergelijkende studie naar de binnensteden van Utrecht, Amsterdam en ’s-Hertogenbosch (Bulletin KNOB, 2011)
From a recent inventory for the Cultural Heritage balance sheet 2009 it is evident that Dutch history of urban planning lacks synthesis and overview. Comparing cities from a historical-spatial point of view is practically virgin territory. It is a challenge to collect, exchange and fit in the many research data resulting from the various disciplines that occupy themselves with the city as a spatial phenomenon. Moreover, the emphasis will have to lie on the agreements between cities and not in the first place on the numerous differences. This article demonstrates what form such a historical-spatial comparison could get. A comparison is made between the three most important cities in the northern Netherlands in the fifteenth and sixteenth centuries: Utrecht, Amsterdam and 's-Hertogenbosch. A theoretical concept from the young interdisciplinary field of Cultural Heritage studies is used for the comparison.The so-called 'historical stratification' of the urbanization process in the three city centres is analysed in a morphological sense and placed within a framework. The objects and structures forming the present cityscapes are thereby attributed to the historical layer in question from which they originated. As the three cities arose at different moments in history, the first phases of the urbanization process are compared diachronically. After Amsterdam had surpassed Utrecht and 's-Hertogenbosch around the middle of the sixteenth century, the comparison is followed synchronically. In this way it proves to be possible to track down some broad outlines in the urbanization process, which have left their traces in each city. These broad outlines are summarized in a schematic framework, from which it is evident that the pre-urban phase chiefly determined the situation and location of a city, the phases of city development chiefly determined the present structure of the city centre, and the various phases of urban planning chiefly determined the present building stock.In addition, the initial impetus is given for possible explanations of the historical stratification by considering the urbanization process from a wider and deeper perspective. The article is intended to serve as a start and handle for further study and comparison of the Dutch urbanization process in the long term. The urban planning-historical knowledge can be supplemented, qualified and improved by looking at more cities from an interdisciplinary point of view and with the historical stratified cityscape as an important source and guideline.